2008
DOI: 10.1677/joe-08-0246
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of small-molecule inhibitors of the sodium iodide symporter

Abstract: The sodium/iodide symporter (NIS) mediates the active transport of iodide from the bloodstream into thyrocytes. NIS function is strategic for the diagnosis and treatment of various thyroid diseases. In addition, a promising anti-cancer strategy based on targeted NIS gene transfer in non-thyroidal cells is currently developed. However, only little information is available concerning the molecular mechanism of NISmediated iodide translocation. Ten small molecules have recently been identified using a high-throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 25 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…ITB5 was shown to be a powerful inhibitor with a half maximal inhibitory concentration (IC 50 ) value of 40 n M . Further analysis of the effect of ITB5 on iodide‐induced current in NIS‐expressing Xenopus oocytes showed that the inhibition was rapid (<5 s) and reversible 8. These results indicated that ITB5 acts by disrupting NIS either directly or at a post‐translational level.…”
Section: Methodsmentioning
confidence: 89%
“…ITB5 was shown to be a powerful inhibitor with a half maximal inhibitory concentration (IC 50 ) value of 40 n M . Further analysis of the effect of ITB5 on iodide‐induced current in NIS‐expressing Xenopus oocytes showed that the inhibition was rapid (<5 s) and reversible 8. These results indicated that ITB5 acts by disrupting NIS either directly or at a post‐translational level.…”
Section: Methodsmentioning
confidence: 89%
“…This expression decreases with increasing doses and increases with time following exposure. Studies have reported different molecules that influence NIS expression, such as pregnancy-associated hormones, among others (47,48). These molecules, when suppressed, such as the MAP kinase and PI3K/Akt pathways, and HDAC, can induce an increase in NIS expression.…”
Section: Discussionmentioning
confidence: 99%
“…Among the samples screened, an EtOH extract of the marine sponge Dysidea sp. also exerted potent inhibitory effects on osteoblastogenesis, and repeated column purification based on this activity led to the isolation of three active constituents [123]: dysidenin (28) [124][125][126], herbasterol (29) [127], and stellettasterol (30) (Fig. 7) [128].…”
Section: Inhibitors Of Bmp-induced Osteoblastic Differentiationmentioning
confidence: 99%